Fertigation effects on elephant foot yam (Amorphophallus paeoniifolius) + greengram (Vigna radiata) intercropping system - JATA, S K; NEDUNCHEZHIYAN, M; MAITY, S K; MALLIKARJUN, M (The Indian Journal of Agricultural Sciences, 2019)
An investigation was carried out during 2013–14 at the research farm of ICAR-Central Tuber Crops Research Institute, Dumuduma, Bhubaneswar, Odisha to study the effects of fertigation on elephant foot yam [Amorphophallus paeoniifolius (Dennst.) Nicolson]+greengram (Vigna radiata L.) intercropping system. The result revealed that the number of pods/plant, seed and haulm yield of greengram were greater in fertigation treatments than soil application. However, greengram responded to fertigation up to N-K2O @80–80 kg/ha. The elephant foot yam corm yield increased with fertigation up to N-K2O @140–140 kg/ha. The corm yield of elephant foot yam and corm equivalent yield of elephant foot yam+greengram intercropping system with fertigation of N-K2O @100–100 kg/ha was comparable with N-K2O @140–140 kg/ha. The fertigation of N-K2O @100–100 kg/ha resulted in increase of 20.1–22.4% corm yield, 19.8–22.3% corm equivalent yield and 19.9–24.4% nutrient use efficiency over soil application of the same quantity of nutrients. The fertigation of elephant foot yam+greengram intercropping system with N-K2O @100–100 kg/ha also resulted in 26.7–28.7% greater net return and higher benefit: cost ratio over soil application of the same quantity of nutrients. The study indicated that fertigation of N-K2O @100–100 kg/ha was sufficient for obtaining optimum yield, returns and nutrient use efficiency in elephant foot yam+greengram intercropping system.